Peran Wanita Tani dalam Penerapan Teknologi Pengelolaan Tanaman Terpadu (PTT) pada Usahatani Jagung di Kecamatan Pringgabaya Kabupaten Lombok Timur - Rini Endang P; IM. Narka Tenaya; NW. Sri Astiti (JURNAL MANAJEMEN AGRIBISNIS, 2014)
The role of women in employment in the agricultural sector which contributed significantly agriculture, but there are all kinds of problems and their influence in the implementation of the management of the combined.Research described a woman ' s role is aimed at farmers, internal and external factors do influence the participation of women, the farmer and analyzing internal and external factors influence the participation of women in the farmers This research was conducted in the central area which is Pringgabaya corn plants in East Lombok Regency, West Nusa Tenggara Province. Retrieval method based on Slovin respondents so that the number of respondents obtained as many as 97 persons, whereas the respondent taking techniques using random sampling method. The method of data collection by means of observation, and interviews, while the data analysis technique used is system skoring, Parcial Least Square (PLS) quantitative and qualitative descriptive. The results showed that women farmers have the role of high technology in the implementation of PTT, internal factors (knowledge and motivation) and external factors (ease of applying the PTT, the ease of accessing information, ease of access to the means of the PTT, and infrastructure production). Internal factors have a greater influence on the role of women farmers in applying the technology of PTT corn when compared to external factors. Suggestion that can be submitted: (1) a women farmer to get more actively in seeking knowledge, information technology, access facilities production and increase the motivation to enhance its role in implementing the technology, (2) the facilitator play in the technological PTT corn to improve performance in a positive perception of the PTT corn crop that women more motivated to implement the technology, (3) the institution and related parties to involve the peasantry in the agricultural activities, especially in the matter of organic substances, harvesting and after harvest.